2013
DOI: 10.1002/ange.201303449
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of McbB, an Enzyme Catalyzing the β‐Carboline Skeleton Construction in the Marinacarboline Biosynthetic Pathway

Abstract: Drei Gene, mcbABC, die für die Biosynthese von Marinacarbolinen zuständig sind, wurden mithilfe von Genom‐Mining, Gen‐Inaktivierung, heterologer Expression, Befütterung und ortsgerichteter Mutagenese aufgeklärt. McbB ist ein neuartiges Enzym für den Aufbau des β‐Carbolinkerns unter Beteiligung einer Pictet‐Spengler‐Cyclisierung; dabei wird E97 für biochemische Aktivität benötigt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Recent studies have revealed that the microbial bC alkaloids are produced by totally different enzyme families from those of plants (Aroonsri et al, 2012;Chen et al, 2013). Among them, the recently reported McbB from Marinactinospora thermotolerans is a novel enzyme in marinacarboline biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that the microbial bC alkaloids are produced by totally different enzyme families from those of plants (Aroonsri et al, 2012;Chen et al, 2013). Among them, the recently reported McbB from Marinactinospora thermotolerans is a novel enzyme in marinacarboline biosynthesis.…”
mentioning
confidence: 99%
“…Among them, the recently reported McbB from Marinactinospora thermotolerans is a novel enzyme in marinacarboline biosynthesis. Based on heterologous gene-expression experiments, McbB was proposed to be a multifunctional enzyme that catalyzes the PS reaction of L-tryptophan and oxaloacetaldehyde, as well as decarboxylation and oxidation reactions, to produce 1-acetyl-3-carboxy-b-carboline (1) and 1-acetyl-b-carboline (2) ( Figure 1) (Chen et al, 2013). However, in some cases the decarboxylation and oxidation of tetrahydro-bC are catalyzed by other proteins such as oxygenase and aromatase (Santos et al, 1998), or even non-enzymatically (Nemet and Varga-Defterdarovic, 2008), to generate partially or fully aromatized bC scaffold.…”
mentioning
confidence: 99%
“…2A and SI Appendix, Table S1). We also inactivated mtdB (encoding a peptidase S15), mtdC (encoding an unknown protein), mtdD (encoding an unknown protein), the orf1 (encoding an inositol-phosphate phosphatase), and orf2 genes using our established λ-RED-mediated PCR-targeting mutagenesis strategy in M. thermotolerans SCSIO 00652 by replacing them with an apramycin resistance gene cassette (33,40). Genotypes of the mutants were confirmed by PCR (SI Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…The type strain was isolated from marine sediment collected from the northern South China Sea (Tian et al 2009). During the last 5 years, Prof. Ju's group have discovered many bioactive metabolites from this taxon (Huang et al 2011;Ma et al 2012;Zhu et al 2012;Zhou et al 2012;Chen et al 2013). The current study reports the isolation of a new species of this genus obtained from a specimen of Salsola ferganica Drob, a traditional Chinese medicinal plant.…”
Section: Introductionmentioning
confidence: 96%